Malaysian household income distribution: a fractal point of view - Fatimah Abdul Razak,; Faridatulazna Ahmad Shahabuddin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Malaysian Household Income Survey data provided by the Malaysian Department of Statistics is used to provide evidence that the upper tails of the household income distribution follows a fractal based distribution known as power-law. Inequality measures are then applied to ascertain the levels of inequality based on this distribution. In addition to that, we analyzed the data in terms of different classes of occupation, obtained power-law exponents for each class and then highlighted the inequality between these classes.